NON-COMPETES IN EMPLOYMENT CONTRACT - THE (UN)JUSTIFIED LIMITATION OF LABOUR FREEDOM - Kuzminac, Mina (Glasnik Advokatske komore Vojvodine, 2022)
The author analyzes normative and practical aspects of non-competes as an employment law institute. The hypothesis set in the paper is that, although non-compete clauses should exist, there is a need to further limit inclusion of such clauses in employment contracts (especially post-contractual non-competes), so there wouldn’t be an unjustified limitation of labour freedom. The goal of the paper is to present the advantages and disadvantages of non-competes from the (opposed) perspectives of employer and employee, and to indicate which provisions in Serbian legal framework should potentially be revised in order to avoid abuse of non-competes by employers in practice. The paper contains an analysis of legal framework in Serbia and a brief overview of solutions from certain European Union countries which could be guidelines for amending Serbian legislation, as well as the analysis of results of survey conducted through questionnaire, showing that employees are not familiar enough with non-competes. Finally, the author conducted an interview with respondents who have, or have had non-competes in employment contract. Based on the interview, it is concluded that employees agree to the non-competes due to fear of not getting the job, despite believing there is no justified basis for such a clause.
Keywords: non-compete clause, employment contract, loyalty to the employer, labour freedom, forced labour.